Impact of Right Ventricular Trabeculation on Right Ventricular Function in Patients With Left Ventricular Non-compaction Phenotype - Kiss, Anna Réka; Gregor, Zsófia; Popovics, Adrián; Grebur, Kinga; Szabó, Liliána Erzsébet; Dohy, Zsófia; Kovács, Attila; Lakatos, Bálint Károly; Merkely, Béla; Vágó, Hajnalka; Szũcs, Andrea (Frontiers in Cardiovascular Medicine, 2022)
Right ventricular (RV) involvement in left ventricular (LV) non-compaction (LVNC) remains unknown. We aimed to describe the RV volumetric, functional, and strain characteristics and clinical features of patients with LVNC phenotype and good LV ejection fraction (EF) using cardiac magnetic resonance to characterize RV trabeculation in LVNC and to study the relationships of RV and LV trabeculation with RV volume and function. This retrospective study included 100 Caucasian patients with LVNC phenotype and good LV-EF and 100 age- and sex-matched healthy controls. Patients were further divided into two subgroups according to RV indexed trabecular mass [RV-TMi; patients with RV hypertrabeculation (RV-HT) vs. patients with normal RV trabeculation (RV-NT)]. We measured the LV and RV volumetric, functional, and TMi values using threshold-based postprocessing software and the RV and LV strain values using feature tracking and collected the patients' LVNC-related clinical features. Patients had higher RV volumes, lower RV-EF, and worse RV strain values than controls. A total of 22% of patients had RV-TMi values above the reference range; furthermore, RV-HT patients had higher RV and LV volumes, lower RV- and LV-EF, and worse RV strain values than RV-NT patients. We identified a strong positive correlation between RV- and LV-TMi and between RV-TMi and RV volumes and a significant inverse relationship of both RV- and LV-TMi with RV function. The prevalence of LVNC-related clinical features was similar in the RV-HT and RV-NT groups. These results suggest that some patients with LVNC phenotype might have RV non-compaction with subclinical RV dysfunction and without more severe clinical features.